The effects of fluid shear stress on proliferation and osteogenesis of human periodontal ligament cells. Issue 4 (29th February 2016) - Zheng, Lisha; Chen, Luoping; Chen, Yuchao; Gui, Jinpeng; Li, Qing; Huang, Yan; Liu, Meili; Jia, Xiaolin; Song, Wei; Ji, Jing; Gong, Xianghui; Shi, Ruoshi; et al.
Abstract: Shear stress is one of the main stress type produced by speech, mastication or tooth movement. The mechano-response of human periodontal ligament (PDL) cells by shear stress and the mechanism are largely unknown. In our study, we investigated the effects of fluid shear stress on proliferation, migration and osteogenic potential of human PDL cells. 6 dyn/cm 2 of fluid shear stress was produced in a parallel plate flow chamber. Our results demonstrated that fluid shear stress rearranged the orientation of human PDL cells. In addition, fluid shear stress inhibited human PDL cell proliferation and migration, but increased the osteogenic potential and expression of several growth factors and cytokines. Our study suggested that shear stress is involved in homeostasis regulation in human PDL cells. Inhibiting proliferation and migration potentially induce PDL cells to respond to mechanical stimuli in order to undergo osteogenic differentiation.